How Do Fruit Bat Seed Shadows Benefit Agroforestry? Insights from Local Perceptions in Kerala, India. (28th October 2015) - Deshpande, Kadambari; Kelkar, Nachiket
Abstract: Old‐world fruit bats are known to provide significant benefits to tropical agroforestry through seed dispersal services. However, the social pathways through which local people perceive and actually utilize these benefits are not well understood. Through interview surveys with plantation owners and farmers in the Western Ghats of Kerala (India), we documented local perceptions and knowledge about the socio‐ecological importance of fruit bat seed dispersal shadows. Respondents' perceptions were highly positive, with greater benefits reported from seed dispersal, than costs from fruit damage by bats. Interestingly, seed aggregation of commercial fruit crops (cashew, areca) by fruit bats was perceived to reduce agricultural labour costs in plantations. Our study demonstrates that local perceptions can offer valuable insights toward understanding the contribution of bat‐generated ecosystem services for tropical agroforestry systems, and in turn may facilitate effective fruit bat conservation.